Delayed Antidepressant Efficacy and the Desensitization Hypothesis - Commons, Kathryn G. (ACS Chem Neurosci, 2019)
Many conventional antidepressants can quickly raise the levels of extracellular serotonin, yet their positive effects on mood ensues only weeks later. This delay in efficacy is a clinical problem that has proven difficult to overcome. Early investigation noted that the initial increases in extracellular serotonin engaged strong feedback inhibition of serotonin neurons via 5-HT(1A) autoreceptors, resulting in a profound reduction in their firing rate. Over the course of chronic treatment, however, firing rate returned to normal and the inhibition via 5-HT(1A) receptor agonists was attenuated. The coincident timeline of these phenomena led to the influential hypothesis that the relationship was causal and that gradual loss of feedback inhibition mediated by 5-HT(1A) receptors was critical to the delayed therapeutic onset. Simple and appealing, the desensitization hypothesis has taken strong hold, yet much of the supporting evidence is circumstantial and there are several observations that would refute a causal relationship. In particular, even though 5-HT(1A) receptors may desensitize, there is evidence that feedback inhibition mediated by remaining receptors persists. That is, baseline serotonin firing rate returns to normal not because of 5-HT(1A) desensitization but rather despite ongoing feedback inhibition. Thus, while 5-HT(1A) receptors remain important for emotional behavior, it may be other slow-adaptive changes triggered by antidepressants that allow for therapeutic effects, such as those involving glutamatergic synaptic plasticity.